Novel Frog Skin-Derived Peptide Dermaseptin-PP for Lung Cancer Treatment: In vitro/vivo Evaluation and Anti-tumor Mechanisms Study - Dong, Ziyi; Hu, Haiyan; Yu, Xianglong; Tan, Li; Ma, Chengbang; Xi, Xinping; Li, Lei; Wang, Lei; Zhou, Mei; Chen, Tianbao; Du, Shouying; Lu, Yang (Frontiers in Chemistry, 2020)
Lung cancer is the major cause of cancer deaths worldwide, and it has the highest incidence and mortality rate of any cancer among men and women in China. The first-line therapy for lung cancer treatment is platinum-based chemotherapy drugs such as cisplatin. However, the application of present chemotherapies is limited by severe side effects, which stimulates the discovery of new drugs with new anti-tumor mechanisms and fewer side effects. Beneficially, many antimicrobial peptides (AMPs) from frog skin have been reported to exhibit potent anti-cancer activities with low toxicity, high selectivity and a low propensity to induce resistance. In this study, we first reported an AMP named Dermaseptin-PP, from a rarely studied frog species, Phyllomedusa palliata. Dermaseptin-PP exhibited selective cytotoxicity on H157, MCF-7, PC-3, and U251 MG cancer cells instead of normal HMEC-1 cells with low hemolytic effect. Furthermore, on subcutaneous H157 tumor model of nude mice, Dermaseptin-PP was found to display potent in vivo anti-tumor activity in a dose-related manner without obvious hepatopulmonary side effects. It is widely accepted that AMPs usually work through a membrane disruptive mode, and the confocal laser microscope observation confirmed that Dermaseptin-PP could destroy H157 cell membranes. Further investigation of mechanisms by flow cytometry assay and immunohistochemical analysis unraveled that Dermaseptin-PP also exerted its anti-tumor activity by inducing H157 cell apoptosis via both endogenous mitochondrial apoptosis pathway and exogenous death receptor apoptosis pathway. Herein, we emphasize that the membrane disrupting and the apoptosis activation effects of Dermaseptin-PP both depend on its concentration. Overall, a novel frog skin-derived AMP, named Dermaseptin-PP, was identified for the first time. It possesses strong antimicrobial activity and effective anti-tumor activity by distinct mechanisms. This study revealed the possibility of Dermaseptin-PP for lung cancer treatment and provided a new perspective for designing novel AMP-based anti-tumor candidates with low risk of cytotoxicity.